AN EMPIRICAL RELATIONSHIP BETWEEN INDIAN CAPITAL MARKET & BANKING SECTOR - T. Mohamed Nishad; K.T. Thomachan (International Journal of Research Science and Management, 2015)
We investigate the relationship between the Stock market and Banking sector in India in this study. The object of the study is to analyze the long run relationship between Banks the represented by bank index of Nifty and composite price of capital market represented by NIFTY. The data used in this study is collected from NSE website. The empirical investigation is carried out using daily data on two stock indices namely the daily stock index of National Stock Exchange named NIFTY and the daily stock index of the entire banking system named BANK NIFTY. A total of 1000 observations have been included in the present analysis. The major statistical tools used in the study are unit root test, Granger causality test, cointegration analysis, impulse response function and error variance decomposition. The objective of the study is to examine whether any long run relationship exists between these two indices. Johansen cointegration analysis accepted the null hypothesis of no cointegration. Granger causality test also ratify the result obtained from cointegration analysis. Impulse response function and error variance decomposition also suggests the absence of any significant relation between the series. Thus we conclude that the movement of the general stock index is not in conformity with the movement of the stock index of the banking sector.